Reimagining Community-Based Financial Participation through Collective Trust and Cooperative Value Systems - Contana, Ni Km. Aristi Priani; Suci, Ni Made (Celebes Scholar pg, 2025)
This study examines the interconnectedness of financial performance and social participation within the Pacingkreman Bali Contana Association, a community-based financial institution grounded in trust, reciprocity, and shared responsibility. Using a descriptive quantitative approach supported by qualitative insights, the research analyses four key indicators of financial performance including Third Party Funds, Loan to Deposit Ratio, Operating Expenses to Operating Income, and Return on Assets. The findings show that these financial ratios are not isolated measures of liquidity, efficiency, or profitability but expressions of deeper social relations. Deposits represent confidence and belonging, loans reflect ethical interdependence, operational costs signify the work of participation, and profitability denotes distributive stability rather than maximisation. The integration of financial data and member narratives reveals that institutional endurance stems from collective trust and moral coherence rather than from technical optimisation. The study concludes that financial sustainability in community-based systems is socially constituted, relying on the circulation of care, participation, and trust that transform economic exchange into shared resilience.